Aplikasi Layanan Bimbingan Kelompok Berbasis Islam untuk Meningkatkan Self Esteem Pada Siswa Kelas XI IPS Sekolah Menengah Atas - Reska; Sofah, Rahmi; Gani, Syarifuddin (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2014)
The purpose of the research is to increase students’ self esteem at class XI IPS in SMA 1 Indralaya through Islam-based group guidance services. This study used action research guidance and counseling. Research subjects consisted of 8 students, with a criterion of selfesteem is medium and self-esteem is low. Instruments of data collection using psychological scale, observation, and interview. Data were analyzed using descriptive quantitative. The process of activity islam-based group guidance still refers to stages of group counselingservices in general but in every stage are accompanied by the adoption of Islam values and are equipped by the usual norms of Islamic mentoring. The results showed increased self esteem before given action shows that negative self-esteem (low and medium category)having given a positive self esteem (medium and high). So it can be concluded that islambased group guidance services can be applied toimprove students’ self esteem.